Evaluation of the performances of six commercial kits designed for dengue NS1 and anti-dengue IgM, IgG and IgA detection in urine and saliva clinical specimens - Andries, Anne-Claire (BMC Infect Dis, 2016)
BACKGROUND: Rapid diagnostic tests (RDTs) have been commercialized in order to help physicians in dengue diagnosis. Until recently, only blood samples were used for those tests but it has been shown in several studies that urine and saliva can also be employed for dengue diagnosis. RDTs for the detection of NS1 antigen and anti-dengue IgG, IgM and IgA in urine and saliva specimens have thus been developed by Standard Diagnostics. The aim of this study was to evaluate the performances these new commercial assays. METHODS: Two panels of clinical specimens were used: one for the evaluation of the NS1-detection devices and the second for the evaluation of the antibody-detection kits. Each panel consisted of urine and saliva specimens collected sequentially from 86 patients with a confirmed dengue infection. A total of 291 saliva and 440 urine samples were included in the NS1-evaluation panel and 530 saliva and 528 urine specimens constituted the antibody-evaluation panel. All samples were tested in parallel by in-house ELISAs and by the commercial RDTs. RESULTS: The RDTs demonstrated an overall sensitivity of 15.5 %/27.9 %/10.7 % for NS1/IgG/IgA detection in urine samples and 20.4 %/ 34.8 %/11 %/6.2 % for NS1/IgG/IgM/IgA detection in saliva samples. Compared to the in-house NS1 ELISA, the results obtained with the NS1 RDT demonstrated a good correlation with urine samples (kappa coefficient: 0.88) but not with saliva specimens (kappa coefficient: 0.28). RDTs designed for antibody detection in saliva and urine were extremely specific (100 %), but less sensitive than the in-house ELISAs (i.e., reduction of the overall sensitivity by 12.2 % for the RDT designed for IgG detection in urine and by 23.7 % for the RDT detecting anti-DENV IgM in saliva). IgM were not detected in urine, either by RDT or ELISA. CONCLUSIONS: Although the RDTs evaluated here offer an apparently attractive approach for dengue diagnosis, this study suggests that these new commercial kits would require further improvement to increase the sensitivity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12879-016-1551-x) contains supplementary material, which is available to authorized users.